852 Differential expression of surface protein-encoding genes highlights therapeutic vulnerabilities of four SCLC subtypes. (9th November 2020) - Park, Elizabeth; Gay, Carl; Allison Stewart, C; Cargill, Kasey; Diao, Lixia; Wang, Qi; Cardnell, Robert; Wang, Jing; Heymach, John; Byers, Lauren
Abstract : Background: Small cell lung cancer (SCLC) is a highly aggressive neuroendocrine malignancy that accounts for 15% of lung cancer diagnoses. The severity of this disease is exacerbated by the fact that there are few therapeutic options, which mostly offer limited clinical benefit, culminating in a 5-year survival rate of Methods: To identify transcriptional subtypes, we used non-negative matrix factorization of gene expression data from 81 SCLC tumors and identified four subtypes largely based on differential expression of the transcription factors ASCL1, NEUROD1, and POU2F3. We hypothesized that these subtypes may underlie unique therapeutic vulnerabilities. We examined differential expression of genes that encode surface-expressed proteins that may be targetable by reagents such as therapeutic antibodies or antibody-drug conjugates (ADCs). Results: Our four subtypes are defined either by high expression of ASCL1 (SCLC-A), NEUROD1 (SCLC-N), POU2F3 (SCLC-P), or an absence of those transcription factors and instead a prevalence of immunological factors (SCLC-Inflamed, or SCLC-I). We curated a list of approximately 60 candidate genes encoding surface proteins that are differentially expressed across the four subtypes. Within these 60 candidates, we have identified a few specific to each subtype for which there exist clinically available, targeted ADCs. The most prevalent subtype, SCLC-A, showed high expression of targets such as DLL3 (SCLC-A) and CEACAM5 (SCLC-A). SCLC-N highly expressed SSTR2, a somatostatin receptor that is being actively targeted in SCLC clinical trials. The two non-neuroendocrine subtypes, SCLC-P and SCLC-I shared some common hits such as the NK cell ligand MICA and B7H6. All of the identified and highlighted hits have been or are actively being pursued in clinical trials, highlighting the importance of understanding their expression levels pre- and post-treatment so that novel therapies can be developed that will be effective over the course of disease progression Conclusions: The underlying biology defining our four identified subtypes of SCLC has revealed a striking number of targetable, differentially expressed surface protein encoding genes many of which already have clinically available reagents that could be repurposed for treatment of SCLC on a subtype-specific basis.